Impact of the cold regenerator mesh geometry on low temperature pulse tube cold finger performance. Issue 1 (March 2020) - Dherbécourt, D; Martin, S; Charles, I; Duval, JM; André, J; Daniel, C
Abstract: Future astrophysics missions such as SPICA, Athena or LiteBird will need a cooling below 1 K (until 50 mK) to achieve the detectors' required sensibility. To address such requirements, cooling chains are built coupling several technologies using intermediate temperature cooling, explaining why a high cooling power at 15 K is essential. The CEA-DSBT designed, for lab test purpose, a Pulse Tube cooler system consisting of a heat intercepted single-stage cold finger which is pre-cooled by a Gifford McMahon cryocooler. The cold part of the PT, in particular the regenerator, is critical to the PT cooler performance. Keeping the regenerator material standard (stainless steel mesh), we study here the influence of the cold regenerator mesh geometry on the operation of the cold finger. The wire thickness is varied, which modifies the porosity, the dead volume and the heat surface exchange of the regenerator. Experimental results on different mesh designs are presented here and analysed, showing a significant influence of the mesh geometry on the performance.